Proceedings DARPA Information Survivability Conference and Exposition II. DISCEX'01
DOI: 10.1109/discex.2001.932166
|View full text |Cite
|
Sign up to set email alerts
|

A framework for managing faults and attacks in all-optical transport networks

Abstract: Fault and attack survivability in all-optical transport networks (AOTNs) require new approaches because of unique transmission characteristics. Specijically, Jiber nonlinearities and network transparency to transmitted signal types may make the network vulnerable to unorthodox attacks. Furthermore, unlike in electronic networks that regenerate signals at every node, attack detection and isolation schemes may not have access to the overhead bits used to transport supervisory information between regenerators o r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…It is also possible for a single point attack on a link to affect not only the first node it reaches, but also other adjacent nodes to which the first node is connected. This attack can be done inexpensively and subtly and can be targeted at individual users [13]. Out-of-band jamming is a type of denial of service attack in which the attacker diminishes the transmission or flow of a signal by exploiting components with cross-talk leaks or cross-modulation effects.…”
Section: Reliability Assessment Of Denial Of Service Due To Coordinatmentioning
confidence: 99%
“…It is also possible for a single point attack on a link to affect not only the first node it reaches, but also other adjacent nodes to which the first node is connected. This attack can be done inexpensively and subtly and can be targeted at individual users [13]. Out-of-band jamming is a type of denial of service attack in which the attacker diminishes the transmission or flow of a signal by exploiting components with cross-talk leaks or cross-modulation effects.…”
Section: Reliability Assessment Of Denial Of Service Due To Coordinatmentioning
confidence: 99%
“…But the binary status of crosstalk levels at a node is simple and often observable. In fact, a frequent scenario for attack detection and monitoring is whether a predetermined threshold or service guarantee is violated at each node [5] [6] [7]. When the amount of cross-talk is below the threshold, the node is "up", i.e., operational; otherwise, the node is "down", i.e., affected.…”
Section: B Probabilistic Attack Propagation Modelmentioning
confidence: 99%
“…Necessary and sufficient conditions for crosstalk attack localization are investigated in [2]. General frameworks for managing faults and alarms in AON are discussed in [5] [6] [7]. All these approaches are reactive in nature.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these methods are too difficult to implement in every AON component or require access to the electrical domain [3]- [5]. Although there are many reasons why crosstalk attacks must be detected and identified at any point in the network where they may occur, it has been shown that it is not necessary to put monitors at all AON nodes [6], [7]. Furthermore, it has been shown that monitoring information for any established lightpath on the input and output sides of each optical cross-connect (OXC) node is sufficient to localize the source of multiple crosstalk attacks and to identify their natures in AONs [8].…”
mentioning
confidence: 99%